Оn the socializing impact of the Internet (at the example of russian and kazakstan students) - Injigolyan, А.А. (Ye.A.Buketov Karaganda State University Publishing house, 2010)
The article is dedicated to research deflected as the Internet on change a way of life of youth influences. As a result, there were determined 6 types of users Internet: the sociable, beginners, qualified users, net users, searching for amusement, utilitarianisms.
Интернеттің əлеуметтендіру ықпалы туралы (қазақ жəне орыс студенттері мысалында)
О социализированном влиянии Интернета (на примере русских и казахстанских студентов)
Keywords: types of users Internet; the sociable; beginners; qualified users; net users; searching for amusement; utilitarianisms